2006
DOI: 10.1093/europace/euj016
|View full text |Cite
|
Sign up to set email alerts
|

Volume measurement by CARTO™ compared with cardiac magnetic resonance

Abstract: Although CMR and CARTO showed a good correlation in the measurement of RVEDV and LVEDV in a group of heart failure patients, the clinical interchangeability of the two methods may be questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…13,14 In the study by van Langenhove et al an underestimation of 20% point was observed for LVEF in comparison with LVA. However, in their study this was explained by an underestimation of EDV by EEM (69.1 ml vs. 125.9 ml), while there was far less difference in ESV.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…13,14 In the study by van Langenhove et al an underestimation of 20% point was observed for LVEF in comparison with LVA. However, in their study this was explained by an underestimation of EDV by EEM (69.1 ml vs. 125.9 ml), while there was far less difference in ESV.…”
Section: Discussionmentioning
confidence: 92%
“…Al-though there have been many studies focusing on the differentiation between viable and non-viable myocardium, to date only a few studies focusing on the diagnostic accuracy of EEM for assessment of global LV function have been published. 13,14 Therefore, we sought to investigate the diagnostic accuracy of EEM in a cohort of post-STEMI patients undergoing routine cardiac catheterisation.…”
mentioning
confidence: 99%
“…The mapping procedure is based on dragging the catheter along the endocardium and sequentially acquiring the location of the tip and local electrograms while in stable contact with the endocardium. The 3-D maps are constructed by combining and integrating the information from the intracardiac electrograms with the respective endocardial locations (Grothues et al 2006).…”
Section: Electro-anatomical Three-dimensional Mappingmentioning
confidence: 99%